Pengaruh Lingkungan Kerja, Penghargaan dan Motivasi Kerja Terhadap Kinerja Guru di Sekolah Menengah Atas Muhammadiyah 10 Surabaya - Imam Sakhroni; Mohammad Soleh; Fauzie Senoaji (Annusfy : Journal of Multidisciplinary Research, 2026)
The purpose of this study was to analyze the influence of work environment, rewards, and work motivation on teacher performance. This study used a quantitative approach with a survey method and data collection through questionnaires. The population in this study consisted of all teachers at SMA Muhammadiyah 10 Surabaya, totaling 65 people, determined using a saturated sampling technique. The data were analyzed using multiple linear regression with the help of SPSS version 29. The results showed that simultaneously, the variables of work environment, rewards, and work motivation had a positive and significant effect on teacher performance. Partially, all three variables also had a significant effect. A comfortable work environment, fair rewards, and high work motivation contribute to improving teacher performance. Therefore, the school is expected to continue developing a supportive work environment, a proportional reward system, and ongoing efforts to motivate teachers